The Question of Caffeine - Natalia Latosinska, Jolanta; Latosinska, Magdalena (IntechOpen, 2017)
Because of its ability to reduce tiredness, sleep deprivation and improve alertness, caffeine emerged in the twenty-first century as a miraculous specific, which allows humans to cross their normal physiological and psychological body limits. Its attractiveness comes from its natural origins and strong psycho-stimulating properties, with relatively weak side effects. Caffeine studies carry the hope to understand the associations between inherited genotype and drug action and to find highly personalized treatments for various diseases, more sophisticated drug delivery systems, safer ways of protecting plants and cheap, renewable fuels. This book consists of chapters covering caffeine history, methods of its determination and not only astonishing medicinal but also non-medicinal applications. It is our hope that every reader will find in this book something interesting, inspiring, informative and stimulating.